2002
DOI: 10.1113/jphysiol.2002.018515
|View full text |Cite
|
Sign up to set email alerts
|

Novel functional properties of Ca2+ channel β subunits revealed by their expression in adult rat heart cells

Abstract: Recombinant adenoviruses were used to overexpress green fluorescent protein (GFP)‐fused auxiliary Ca2+ channel β subunits (β1‐β4) in cultured adult rat heart cells, to explore new dimensions of β subunit functions in vivo. Distinct β‐GFP subunits distributed differentially between the surface sarcolemma, transverse elements, and nucleus in single heart cells. All β‐GFP subunits increased the native cardiac whole‐cell L‐type Ca2+ channel current density, but produced distinctive effects on channel inactivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
255
3
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(280 citation statements)
references
References 85 publications
17
255
3
5
Order By: Relevance
“…Cultured adult guinea pig cardiomyocytes typically exhibited large I CaL densities in the presence of β 2a -GFP, consistent with previous reports [24,26,27]. However, cells transduced with α 1c-D-, in addition to β 2a -GFP, showed a larger I CaL density than those infected with β 2a -GFP alone (Fig.…”
Section: Expression Of α 1c-d-in Cardiac Myocytessupporting
confidence: 90%
See 2 more Smart Citations
“…Cultured adult guinea pig cardiomyocytes typically exhibited large I CaL densities in the presence of β 2a -GFP, consistent with previous reports [24,26,27]. However, cells transduced with α 1c-D-, in addition to β 2a -GFP, showed a larger I CaL density than those infected with β 2a -GFP alone (Fig.…”
Section: Expression Of α 1c-d-in Cardiac Myocytessupporting
confidence: 90%
“…In these experiments, we co-expressed the rat β 2a subunit (fused to GFP), as it has previously been demonstrated that β subunit coexpression is a limiting factor for L-type Ca 2+ current density in cultured adult cardiomyocytes [24,26,27]. In preliminary experiments, we also observed that I CaL declined markedly over 48 h in culture in the absence of β subunit over-expression (data not shown).…”
Section: Expression Of α 1c-d-in Cardiac Myocytesmentioning
confidence: 74%
See 1 more Smart Citation
“…The G402S and G406R mutations were introduced by sitedirected mutagenesis using Quikchange (Stratagene). Ca V ␤ 2b and Ca V ␣ 2 ␦ 1 are the accessory subunits associated with Ca V 1.2 in the human heart (7,8). The rabbit Ca V ␤ 2b and Ca V ␣ 2 ␦ 1 clones used for expression in Xenopus oocytes were a kind gift from N. Dascal (Tel Aviv University, Ramat Aviv, Israel).…”
Section: Methodsmentioning
confidence: 99%
“…Voltage-gated L-type Ca 2ϩ channels are multisubunit complexes composed of a poreforming ␣ 1 subunit and auxiliary ␤ and ␣ 2 ␦ subunits (4). In cardiac muscle, a distinct ␣ 1 subunit (␣ 1 1.2a) (5,6), an ␣ 2 ␦ subunit (7), and several isoforms of ␤ subunits [␤ 1b and ␤ 2a-d (8)(9)(10)(11)] have been identified and implicated to form the Ca V 1.2 channel. As for the skeletal muscle Ca V 1.1 channel (12,13), two size forms of the ␣ 1 1.2a subunit of Ca V 1.2 channels, Ϸ240 and 210 kDa, are present in cardiac muscle and differ by truncation at the C terminus (14).…”
mentioning
confidence: 99%